Multijurisdictional firms and governments' strategies under alternative tax designs - Marcel Gérard (Center for Economic Studies and ifo Institute (CESifo), 2005)
Conducted in a framework which embodies tax-shifting opportunities, risk of losses and possibility of interjurisdictional loss-offset, this paper investigates a reform of multijurisdictional enterprises taxation, a move from Separate Accounting to Formulary Apportionment. Findings are summarised in a series of propositions on the strategic behaviour of enterprises and authorities. Under Separate Accounting, tax-shifting opportunities reduce investment in the lower-taxing jurisdiction, tax sensitivity of investment and tax competition. Moving to Formulary Apportionment eliminates such opportunities, pushing the economy in the opposite direction. Permitting the firm to compensate losses among affiliates allows it to benefit from a tax-shifting and insurance device.
Keywords: H87; H73; H32; 330; multijurisdictional enterprise; separate accounting; formulary apportionment; cross-border loss offset; Körperschaftsteuer; Unternehmensbesteuerung; Doppelbesteuerung; Multinationales Unternehmen; Transferpreis; Steuerwettbewerb; Besteuerungsgrundsatz; Theorie; formula apportionment